Understanding changes in cassava root dry matter yield by different planting dates, crop ages at harvest, fertilizer application and varieties - Enesi, R.; Hauser, S.; Pypers, P.; Kreye, C.; Tariku, M.; Six, Johan (Elsevier, 2022)
Cassava is a perennial crop that can adapt to periods of drought at different times in a growing season, which permits scheduling planting and harvest to develop production systems supplying roots continuously. However, farmers plant and harvest cassava at the onset of rains which creates glut and results in unattractive root prices. Thus, farmers need to understand how cassava varieties respond to different planting dates and crop ages at harvest to be able to use opportunities in income generation that may arise from flexible planting and harvest dates resulting from price and dry matter (DM) variabilities. Thus, this study was conducted to identify the best time to plant and harvest cassava for different varieties (TME419 and TMS581) and to determine the effect of fertilizer on root DM yields in three locations (Idi-Ose, Moniya and Ido) in Nigeria, over two years. The overall objective was to provide information to guide farmers on how to schedule planting and harvesting in Nigeria. The trials were conducted using a factorial split-split plot design. Effects of early, mid and late planting dates combined with harvest at 9, 11 and 13 months after planting (MAP) were tested. Fertilizer treatments included a control (F0) and applications of 75 kg N ha−1, 20 kg P ha−1 combined with 90 (F1), 135 (F2) and 180 (F3) kg K ha−1. A root DM yield increase of 44.8% was observed when crop age increased from 9 to 11 MAP, and an increase of 13.1% when crop age increased from 11 to 13 MAP, indicating that delaying harvests does increase root DM yield across all planting dates. In contrast, root DM yield differences between planting dates were marginal, an increase of 8.1% was observed from early to mid-planting date and of 9.5% from early to late planting dates. Fertilizer treatments significantly interacted with location and the largest responses were observed at Ido. Fertilizer increased cassava root DM yields when compared with control at Ido by 15.38%, 23.1% and 16.7% in F1, F2 and F3, respectively. Responses were inconsistent at Moniya and Idi-Ose. With information on the effect of crop age and fertilizer, farmers could benefit from targeting seasons with shortage of cassava roots and high cassava prices, which would benefit processing industries securing year-round root supply.